Contrasting effects of reindeer grazing on CO2, CH4, and N2O fluxes originating from the northern boreal forest floor - Köster, Kajar; Köster, Egle; Berninger, Frank; Heinonsalo, Jussi; Pumpanen, Jukka (Land Degradation & Development, 2020)
Reindeer (Rangifer tarandus L.) is considered to be an important mammalian herbivore, strongly influencing Arctic lichen-dominated ecosystems. There is no wide knowledge about the effect of reindeer on greenhouse gas (GHG) fluxes in northern boreal forests. Ground vegetation plays an important role in absorbing nitrogen (N) and carbon dioxide (CO2) from the atmosphere. Lately, it has also been found to be a significant source of nitrous oxide (N2O) and a small source of methane (CH4). We investigated the influence of reindeer grazing on field layer GHG (CO2, CH4, and N2O) fluxes, ground vegetation coverage and biomass, and soil physical properties (temperature and moisture) in a northern boreal forest. At our study site, the reindeer-induced replacement of lichen by mosses had contrasting effects on the GHG fluxes originating from the field layer. Field layer CO2 efflux was significantly higher in grazed areas. The field layer was a CH4 sink in all areas, but grazed areas absorbed more CH4 compared to non-grazed areas. Although total N2O fluxes remained around 0 in grazed areas, a small N2O sink occurred in non-grazed areas with lower moss biomass. Our results indicated that grazing by reindeer in northern boreal forests affects GHG fluxes from the forest field layer both positively and negatively, and these emissions largely depend on grazing-induced changes in vegetation composition. Peer reviewed